PENERAPAN GREEN GRK TERINTERGRASI GOVERNANSI, RISIKO, KEPATUHAN BADAN PENGELOLA KEUANGAN DI INDONESIA NON PERBANKAN - Sugiyanto Sugiyanto; Rachmat Kartolo (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2023)
Implementation of GRC (Governance, Risk, Compliance) is a must. With the implementation of integrated GRC, it is expected to achieve principled performance through handling uncertainty and full integrity actions within Organitation, to implement integrated green GRC. This study aims to assess the company's readiness in the assessment green GRC, preparing supporting infrastructure, and making development plans for integrated GRC implementation. To achieve this goal, several methodologies were established, namely conducting a perception survey through questionnaires, reviewing guidelines and policy documents relevant to the integrated system, interviews with leaders, and the Delphi Method to obtain an agreement on proposals. In phase 1, a gap analysis was conducted on green GRC practices. Phase 2: Integrated green GRC System Infrastructure Design Based on the results of a study on the readiness for integrated GRC implementation Phase 3: Integrated GRC Implementation Plan Study phase, the identified gaps will be formulated into a concept. This is indicated by the high perception generally stating that it has developed on various aspects in the green GRC field that currently exist in However, based on the documentation, there are still document gaps as the basis for implementing integrated GRC. For this reason, as part of the implementation of integrated GRC along with its development plan in accordance with compliance